2006
DOI: 10.1016/j.healthplace.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Pokies and poverty: problem gambling risk factor geography in New Zealand

Abstract: Up to 2% of adults in New Zealand can be considered problem gamblers, where the activity has an impact on the well-being of those who gamble, and often their close associates. The most common activity involves non-casino gaming machines (NCGMs). This paper explores the geography of gambling 'opportunity' at small-area scales, and finds excess provision in those areas classified as highly deprived. Geographically weighted regression has been used to investigate the possibility that the degree of inequity in NCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 7 publications
7
61
0
1
Order By: Relevance
“…Only recently has the role of regulatory and legislative changes received broader attention in relation to its (potential) impact upon the unequal distribution of gambling opportunities. As Wheeler et al (2006) note, in other areas of 'addictive' health behaviours policy often trails research and this appears to be the case with gambling. Crucially, whilst there is widespread acceptance of problem gambling as a psychiatric disorder and a recognition its prevalence should be minimised, a public health based approach to policy in Britain has not been adopted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently has the role of regulatory and legislative changes received broader attention in relation to its (potential) impact upon the unequal distribution of gambling opportunities. As Wheeler et al (2006) note, in other areas of 'addictive' health behaviours policy often trails research and this appears to be the case with gambling. Crucially, whilst there is widespread acceptance of problem gambling as a psychiatric disorder and a recognition its prevalence should be minimised, a public health based approach to policy in Britain has not been adopted.…”
Section: Discussionmentioning
confidence: 99%
“…The British Gambling Prevalence Survey 2010 showed that the prevalence of playing gambling machines was significantly higher among those who were unemployed, had low personal income and/or were living in areas of greatest deprivation (Wardle et al, 2011). As noted in other jurisdictions, a majority of those presenting for treatment for gambling problems are heavily involved in machine play (Wheeler et al, 2006;GamCare, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for this situation, ArcMap10's Geographically Weighted Regression (GWR) tool runs a regression for each feature (Area Unit) rather than the study area as a whole, allowing model coefficients to vary regionally (Brunsdon, Fotheringham, & Charlton, 1998;Mitchell, 2005). Previous accessibility-related applications of GWR include examination of geographical factors and problem gambling (Wheeler et al, 2006) …”
Section: Geographically Weighted Regressionmentioning
confidence: 99%
“…While the majority of gamblers in a given population gamble within their personal and financial limits, a proportion gamble excessively and experience a variety of difficulties (Wheeler et al 2006, Korn et al 2003.…”
Section: (Statistics Canada 2006a)mentioning
confidence: 99%